KONSEP PEMIKIRAN PENDIDIKAN ISLAM PERSPEKTIF AHMAD TAFSIR - Nabila, Ahsana; Barizi, Ahmad (IAIN Kendari, 2024)
This article aims to help teachers understand in depth teaching because in this case it is very important and also has a big influence on learning outcomes or student output. Of course, in this case the author relates the perspective of a figure who is no longer in doubt in the world of education, namely Ahmad Tafsir. This article explains in detail how to become a teacher who understands the nature of teaching. This research uses the library research method with research results a) understanding teaching methods b) understanding educational theory other than teaching theory c) formulating teaching objectives d) teaching procedures e) planning evaluation. It is hoped that the points that have been explained by the author can change patterns of thinking and also help improve teaching in order to advance education in Indonesia.